Analysis of Disaster Education Models: Studies from Early Childhood to Higher Education Levels - Elvara Norma Aroyandini; Ani Rusilowati; Supriyadi Supriyadi; Hartono Hartono; Bambang Subali; Nur Hamid; Juhadi Juhadi (Universitas Negeri Semarang, 2023)
Disaster education is a mandatory effort to deal with unexpected natural disasters. Disaster education trains knowledge, attitudes, and skills in dealing with disasters, one of which can be done through formal education, starting from early childhood to tertiary education. This writing aims to analyze the model of implementing disaster education through formal education, starting from early childhood education, elementary school, and middle school, to university. This article systematically uses the type of literature review writing by reviewing as many as 53 articles in Scopus-indexed journals and proceedings. The research results show different disaster education models at each level. The early childhood education level is taught with fun learning activities inside and outside the classroom, telling stories, and through websites. Elementary school level is carried out by camping, disaster drills, integrated with learning and local wisdom, implementing programs in schools, and optimizing smartphone functions. The secondary school level is conducted by conducting preparedness exercises, optimizing smartphones, applying specific learning methods, and integrating them with subjects. As for the tertiary level, this can be done by being involved in management, in natural disaster areas, and making disaster education a compulsory subject.